Penerapan Performance-Based Navigation Dan Automatic Dependent Surveillance–Broadcast Dalam Meningkatkan Efisiensi Lalu Lintas Udara Di Wilayah Indonesia - Rizqullah Dzaky Prawira Handono; I Gede Farrel Raditya Pranajaya; Dhian Supardam; Lina Rosmayanti (Politeknik Penerbangan Indonesia Curug, 2026)
Improving air traffic efficiency is one of the main challenges in Indonesia’s air transportation system, which covers a vast and complex airspace. This study discusses the implementation of Performance-Based Navigation (PBN) and Automatic Dependent Surveillance–Broadcast (ADS–B) as solutions to enhance the effectiveness of national airspace management. The methods used include a descriptive analysis of civil aviation policies, case studies of implementation in several Indonesian airspace sectors, and evaluation of the resulting improvements in operational efficiency. The results show that the application of PBN can optimize flight routes, reduce fuel consumption, and increase airspace capacity. Meanwhile, the use of ADS–B enhances real-time surveillance and monitoring capabilities, especially in remote areas not yet covered by conventional radar. The combination of these two technologies contributes significantly to improving flight safety, efficiency, and punctuality in Indonesia. Therefore, continuous implementation, along with infrastructure and human resource support, are key factors in the success of future performance-based navigation and surveillance systems.